WOMEN STEREOTYPE IN “LEGALLY BLONDE” MOVIE - Hayah, Lia Maisyuratul; Mustikawati, Yunitari (Journal of English Literature and Linguistic Studies, 2023)
Gender stereotypes are views or beliefs that are generally applied to men and women within a culture or society. This research aims to analyze the aspects and meanings of gender stereotypes in Legally Blonde movie. The research uses a descriptive qualitative method and is analyzed using a feminist approach. The research findings indicate that the movie Legally Blonde presents various stereotypes about women. However, the main character in the movie, Elle Woods, successfully challenges and proves herself to be a woman who is not only glamorous and feminine, but also intelligent and capable of studying law at Harvard and becoming a lawyer. The research concludes that stereotypes in the film can be harmful and limit opportunities available to women in real life. By challenging these stereotypes, Legally Blonde encourages audiences to see women beyond their physical appearance or social roles. Appearance cannot be an indicator of one's intelligence and abilities.